Multiprocessor systems-on-chips - Jerraya, Ahmed Amine, ....-; Wolf, Marilyn Claire, 1958- (Amsterdam : Elsevier, 2005)
Table of Contents 1. The What, Why, and How of MPSoCs* Part I. Hardware 2. Techniques for Designing energy-Aware MPSoCs* 3. Networks on Chips*4. Architecture of Embedded Microprocessors* 5. Performance and Flexibility for Multiple-Processor SoC Design*6. MPSOC Performance Modeling and Analysis*7. Design of Communication Architectures for High-Performance and Energy Efficient System-on-Chips* 8. Design space exploration of on-chip networks* Part II. Software 9. Memory Systems and Compiler Support fo MPSoC Architectures*10. A SystemC-Based Abstract Real-Time Operating System Model for Multiprocessor System-on-Chip*11.Cost-Efficient Mapping of Dynamic Concurrent Tasks in Embedded Real-Time Multimedia Systems*12. ILP-Based Resource-Aware Compilation* Part III. Methodologies and Applications 13. Component-Based Design for Multiprocessor System-on-chip*15. Models of Computation for Systems-on-Chips* 16. Metropolis: A Design Envrionemnet for Heterogenous Systems* Glossary*Bibliography*Contributors
Marilyn Claire Wolf was born as Wayne Hendrix Wolf